2004
DOI: 10.1136/bmj.38093.646215.ae
|View full text |Cite
|
Sign up to set email alerts
|

Soya food intake and risk of endometrial cancer among Chinese women in Shanghai: population based case-control study

Abstract: Objective To evaluate the association of intake of soya food, a rich source of phytoestrogens, with the risk of endometrial cancer. Design Population based case-control study, with detailed information on usual soya food intake over the past five years collected by face to face interview using a food frequency questionnaire. Setting Urban Shanghai, China. Participants 832 incident cases of endometrial cancer in women aged of 30 to 69 years diagnosed during 1997-2001 and identified from the Shanghai Cancer Regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
2
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 23 publications
(25 reference statements)
6
56
2
1
Order By: Relevance
“…An association of soyfood with endometrial cancer has been previously reported (Xu et al, 2004). Soyfood was, therefore, not included as an independent food group in the subsequent food group analyses.…”
Section: Resultsmentioning
confidence: 99%
“…An association of soyfood with endometrial cancer has been previously reported (Xu et al, 2004). Soyfood was, therefore, not included as an independent food group in the subsequent food group analyses.…”
Section: Resultsmentioning
confidence: 99%
“…29 This study also reported a significant inverse association with intake of isoflavones, the other major group of phytoestrogens in the human diet, with an OR of 0.59 (95% CI 5 0.37-0.93) for the highest versus lowest quartile, a result in agreement with 2 casecontrol studies that examined the association of intake of soy, the main source of isoflavones, with endometrial cancer risk. 30,31 In our analyses adjusted for body mass index, ORs among preand postmenopausal women appeared to diverge, with ORs below 1 in premenopausal women and above 1 in postmenopausal women. However, our a priori hypothesis was that a protective effect would be observed in both pre-and postmenopausal women, the test for trend was not significant in either menopausal group, nor was the test of interaction by menopausal status.…”
Section: Discussionmentioning
confidence: 96%
“…There is growing evidence from epidemiological and case-control studies that higher intake of plant flavonoids reduces the risk of chronic diseases including cancer (70,71). In contrast, consumption of flavonoid-free diets by healthy human volunteers has been reported to lead to a decrease in markers of oxidative stress in blood viz.…”
Section: Apigenin and Cancermentioning
confidence: 99%